A two miRNA classifier differentiates follicular thyroid carcinomas from follicular thyroid adenomas. (5th January 2015) - Stokowy, Tomasz; Wojtaś, Bartosz; Krajewska, Jolanta; Stobiecka, Ewa; Dralle, Henning; Musholt, Thomas; Hauptmann, Steffen; Lange, Dariusz; Hegedüs, László; Jarząb, Barbara; Krohn, Knut; Paschke, Ralf; et al.
Highlights: Diagnostic limitations of FNA can be partially overcome by molecular analyses. Sixty-eight differentially expressed miRNAs were identified comparing FTCs and FAs. A two-miRNA-classifier resulted in a sensitivity of 82% and a specificity of 49%. The miRNA-classifier might improve the pre-surgical diagnostics of thyroid nodules. Abstract: The inherent diagnostic limitations of thyroid fine needle aspiration (FNA), especially in the "indeterminate" category, can be partially overcome by molecular analyses. We aimed at the identification of miRNAs that could be used to improve the discrimination of indeterminate FNAs. miRNA expression profiling was performed for 17 follicular carcinomas (FTCs) and 8 follicular adenomas (FAs). The microarray results underwent cross-comparison using three additional microarray data sets. Candidate miRNAs were validated by qPCR in an independent set of 32 FTCs and 46 FAs. Sixty-eight differentially expressed miRNAs were identified. Thirteen miRNAs could be confirmed by cross comparison. A two-miRNA-classifier was established improving the diagnostic applicability and resulted in a sensitivity of 82% and a specificity of 49%. We present a classifier that has the potential to be successfully evaluated in cytology material for its capability to discriminate (mutation negative) indeterminate cytologies and thereby improving the pre-surgical diagnostics of thyroid nodules.